2015
DOI: 10.1007/s11102-015-0691-0
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of long-term treatment with Pegvisomant: analysis of Spanish patients included in global ACROSTUDY

Abstract: ACROSTUDY carried out with the Spanish cohort confirmed that PEG has a favorable safety and efficacy profile. The percentage of patients considered under control was similar to data reported globally and in other local ACROSTUDY results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
14
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
9
14
1
1
Order By: Relevance
“…The pituitary MRI findings in this analysis were consistent with the previously reported data for ACROSTUDY (5,9,10,11,12,13,14,15,16). In a retrospective analysis of 75 patients in two centers in the United Kingdom, one patient was reported to have significant tumor size increase; however, this tumor was growing prior to PEGV treatment (17).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The pituitary MRI findings in this analysis were consistent with the previously reported data for ACROSTUDY (5,9,10,11,12,13,14,15,16). In a retrospective analysis of 75 patients in two centers in the United Kingdom, one patient was reported to have significant tumor size increase; however, this tumor was growing prior to PEGV treatment (17).…”
Section: Discussionsupporting
confidence: 89%
“…Serum IGFI normalization rate increased over time (up to 73% in year 10). While this rate is somewhat lower than what was seen in clinical trials, it is similar to what was observed in the first interim analysis and other ACROSTUDY publications (3,4,9,10,11,12,13,14,15,16). Possible explanations for the discrepancy in IGFI control between clinical trials and ACROSTUDY include the use of different criteria for IGFI normalization, absence of a dose titration scheme (as typically done in clinical trials), use of a variety of IGFI assays, the fact that a number of patients with an elevated IGFI were not titrated up to the maximal allowed daily dose according to the label, and that the normalization rate was assessed on a yearly basis in this database rather than at only one time point typical for the primary outcome in clinical trials.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The present data are in broad agreement with previous observations. These data affirm previous reports on the safety of pegvisomant therapy, which have been overall reassuring (22,23). In agreement with previous publications, pegvisomant therapy does not appear to predispose to tumor progression (22).…”
Section: Discussionsupporting
confidence: 92%